Democratic Advisory Committee Policy Statement on Vietnam War (1967)
A policy statement from the Democratic Advisory Committee's Foreign Policy Committee outlines its position on the Vietnam War. It affirms that the Johnson Administration's goals—ending hostilities, shifting from military to economic aid, and achieving a negotiated settlement for a stable, neutral South Vietnam—are attainable. The committee proposes an immediate, unconditional halt to the bombing of North Vietnam to facilitate negotiations. It recommends returning primary combat responsibility to South Vietnamese forces and initiating talks that include the National Liberation Front and the governments of North and South Vietnam, with provisions for self-determination and phased troop withdrawals. The statement also calls for continued economic assistance to both North and South Vietnam to support reconstruction and maintain peaceful, neutral conditions.